Greenloop: a feasibility study on plantable recycled paper bags with embedded seeds - Aguilar, Marjorie A. Coderias, John Eduard M. Jimenez, Alexis Joyce B. Ortiguesa, Monica N. Talao, Ryza L. 4 0 16; 5
u
Feasibility Study : (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2